Altered Lower Limb Kinematics during Jumping among Athletes with Persistent Low Back Pain - Rahman Sheikhhoseini; Mohammad-Hossein Alizadeh; Mahyar Salavati; Kieran O'Sullivan; Elham Shirzad; Marzieh Movahed (The Society of Aging and Physical Activity (SAPA), 2018)
Background. The kinematics of a controlled functional task in female volleyball athletes may be an interesting area of study. Therefore, investigating if there are kinematic changes in a jump landing jump task among female athletes with low back pain (LBP) may help therapists and trainers better prevent and/or rehabilitate LBP in athletes. Objectives. The purpose of this study was to examine lumbopelvic and lower extremity kinematics in athletes with persistent LBP during a jumping task. Methods. A comparative cross sectional study conducted in a university research laboratory. Professional female volleyball players with (n = 20) and without (n = 18) LBP were recruited from the Iranian female volleyball league. To reduce heterogeneity, one particular subgroup of athletes with LBP were selected. Kinematic data including lumbar extension, hip flexion, rotation and adduction and knee flexion and abduction angles when the center of mass was at minimum height during a jump-landing-jump maneuver were collected using a Vicon motion analysis system and analysed using MATLAB software. Independent t-tests were used to compare mean values between the groups. Results. Athletes with LBP had significantly greater hip flexion (LBP: -73.62±11.06˚; Control: -62.88±7.03˚, p=0.016) and significantly less knee flexion (LBP: 77.06±7.27 ˚, Control: 81.62±4.70 ˚, p=0.029) at the lowest point of the jump than athletes without LBP. There were no other significant differences between the groups (p>0.05). Conclusion. A subgroup of female athletes with LBP display altered lower extremity kinematics during a jump task than athletes without LBP. This may have important implications for lower limb performance and injury.